Britannica Student Encyclopedia 1 - Encyclopedia Britannica Inc. (Encyclopedia Britannica Inc., 2007)
Entertaining and informative, the new Britannica Student Encyclopedia helps children gain a better understanding of their world. More than 2,250 captivating articles are the perfect resource for homework help and assignments adn for satisfuing the curiosity of young learners. Children are sure to immerse themselves in 2,700 photos, charts, and tables that help explain concepts and subjects, as well as 1,200 maps and flags from across the globe. Topics to Satisfy Every Curious Learner: A variety of articles-covering geopgraphy, history, nature, sports, religions, the arts, science, and other key subjects-will appeal to all students. Knowledge Is Easily Accessible: A clear organization offers students several ways of looking up information, including A to Z articles and an index. Fun Features for Young Learners: Timelines, More to explore, and Did You Know? features intrigue children and encourage them to keep learning, questioning, and wondering.